Effect of percutaneous vertebroplasty through UTPP approach on prognosis and quality of life in elderly patients with osteoporotic vertebral compression fractures: a retrospective study - Xuejie Bi; Liude Zhou; Tian Chen; Zhuming Chen; Zhi Peng (BMC Surgery)
Abstract Background To explore the clinical characteristics of percutaneous vertebroplasty (PVP) via unilateral transverse process-pedicular (UTPP) approach in the treatment of osteoporotic vertebral compression fracture (OVCF) in the elderly. Methods A total of 120 elderly patients with lumbar OVCF who underwent PVP via unilateral pedicular (UTP) and UTPP approaches in our hospital from January 2022 to January 2024 were retrospectively analyzed. The postoperative VAS score (visual analog scale), ODI score (Oswestry disability index), surgical indicators, and imaging indicators were recorded in the two groups. Results The VAS scores and ODI scores of the two groups of patients were lower than those before surgery 1 day, 6 months, and 12 months after surgery (P < 0.05). The amount of bone cement (BC) injected in the UTPP group was greater than that in the UTP group, the excellent BC distribution rate was higher than that in the UTP group, and the BC leakage rate was lower than that in the UTP group (all P < 0.05). The vertebral anterior edge height and Cobb angle of the UTPP group were significantly different from those of the UTP group 1 day after surgery (P < 0.05). Conclusions After UTPP-PVP, BC is fully diffused, the BC leakage rate is low, and the analgesic effect is good, which can enable patients to get out of bed early and improve their quality of life.